Smart growth how to grow your people to grow your company - Johnson, Whitney (Boston Harvard Business Review Press, 2022)
Growth is the goal. Helping people develop their potential--enabling them to articulate and become the self they want to be, are capable of being, and that best serves them and others in the short and long term--is what we as individuals and leaders strive toward. . . . As individuals grow, so do organizations and societies. Growth is learning put into action--action that betters the world as we better ourselves and our small niches, both personal and professional, within it. Growth occurs when learning is internalized--when we try something new and invest the effort to move it from being something we do to something we are
Includes bibliographical references (pages 201-210) and index.
Keywords: Employees--Coaching